PERSEPSI SISWA TERHADAP PEMBELAJARAN MATEMATIKA BERBASIS NILAI-NILAI KEISLAMAN DI SMPN 2 LANGSA - Faisal, Faisal (Al-Khawarizmi, 2019)
Applying Islamic values are an important part of teaching and learning. The purpose of this study was to determine students’ perception towards teaching mathematics based Islamics values. The research instrument used was a questionnaire. The subject as students grade VII 1 SMPN 2 Langsa. Research metholodogy used was descriptive qualitative method. The result study showed that the percentages of students’ perception towards applying Islamic values on teaching mathematics were 51% strongly agree, 40% agree, 7% less agree, and 2% disagree.